2021
DOI: 10.3748/wjg.v27.i38.6387
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors specificity protein and nuclear receptor 4A1 in pancreatic cancer

Abstract: Specificity protein (Sp) transcription factors (TFs) Sp1, Sp3 and Sp4, and the orphan nuclear receptor 4A1 (NR4A1) are highly expressed in pancreatic tumors and Sp1 is a negative prognostic factor for pancreatic cancer patient survival. Results of knockdown and overexpression of Sp1, Sp3 and Sp4 in pancreatic and other cancer lines show that these TFs are individually pro-oncogenic factors and loss of one Sp TF is not compensated by other members. NR4A1 is also a pro-oncogenic factor and both NR4A1 and Sp TFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In addition to being a target gene of microRNA, FOXF2 is upregulated by specificity protein 1 (SP1), myc-associated zinc-finger protein (MAZ), TGF-β and MCM3AP-AS1 (35)(36)(37)(38). Safe, Shrestha, Mohankumar, Howard, Hedrick and Abdelrahim (39) found that SP1 accelerates cell proliferation and migration of PC cells. MAZ is reported to promote invasiveness of PC cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a target gene of microRNA, FOXF2 is upregulated by specificity protein 1 (SP1), myc-associated zinc-finger protein (MAZ), TGF-β and MCM3AP-AS1 (35)(36)(37)(38). Safe, Shrestha, Mohankumar, Howard, Hedrick and Abdelrahim (39) found that SP1 accelerates cell proliferation and migration of PC cells. MAZ is reported to promote invasiveness of PC cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…TF is important regulators of intrinsic life processes within cells, possess DNA-binding domains and initiate transcription of genes [ 30 ]. Over the years, a large amount of data from different laboratories has shown that TFs are involved in progression of cancer [ 31 33 ]. For instance, FoxO1 promotes glioma cell proliferation by acting as a transcriptional activator of RFC2 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These TFs might be important factors in the pathogenesis of RF. While Sp2, Sp3, and Sp4 were associated with cell proliferation, survival, migration, and invasion and highly expressed in tumors ( Zhao et al, 2014 ; Kim et al, 2017 ; Safe et al, 2021 ), their roles in fibrosis have yet to be reported. Whether and how these TFs participate in the pathogenesis of RF remain to be further studied.…”
Section: Discussionmentioning
confidence: 99%